Beckett's Metatheatrical Philosophy: A postmodern Tendency Regarding Waiting for Godot and Endgame - Keshavarz, Marzieh (Mediterranean Journal of Social Sciences, 2012)
There are so many controversial debates over the features of Beckett's dramatic works that surpass the previous models ofliterary plays. Andrew K. Kennedy (1991) asserts that "what is unique is the supreme fiction that turns so many disparate ideas,impulses, beliefs, and unbeliefs into a new and personal mythology" (3). Thus, the main concern of this paper concentrates on Beckett'sphilosophy that breaks with the conventional principles of theatre in order to promote a new view of dramatic form which Lionel Ablecoins as metatheatre. Abel constructs his notion of metatheatre on two famous phrases which are 'the world is a stage' and 'life is adream' that justify the dreamlike atmosphere of Beckett's plays. Beckett's plays that at the first glance seem nonsense or meaningless,demand a deeper awareness and should be evaluated by destructing the conceptual boundaries as they are constructed upon thedeviation from the standard norms. His plays insist that the ultimate reality of one's mind is beyond the limits of logical mind. Hence theword meta- theatre is suitable for his plays, because the basic idea of meta- theatre is that of multiple layers of meaning. Beckett'stheatrical masterpieces, Waiting for Godot and Endgame are among the best examples of falling away from the accepted standards.Still, the loose structure of the plays with little or no action in which a few anti - heroes play out their roles in a nightmarish world ofmotionless time does not make it pessimistic. As Brook (1990) says, "Beckett's dark plays are plays full of light" (65). Waiting for Godotand Endgame in particular will lead us to advance the central argument and achieve a more comprehensible analysis of Beckett’s majorplays.